Perinatal Hypoxic-Ischemic Encephalopathy: epileptic and paretic outcome at one year of age - Allemand Federico; Reale Federica; Sposato Marco; Allemand Alessandro (BMC, 2009)
Abstract Background The issue concerning neurologic outcome in patients with perinatal Hypoxic-Ischemic Encephalopathy (H.I.E) has inspired many studies which tried to identify adequate prognostic factors. Our work aims to find among neonatal parameters: - factors which help to predict the risk to develop both Cerebral Palsy (CP) and secondary Epilepsy at one year of age in subjects affected by perinatal Hypoxic-Ischemic Encephalopathy, - correlations between the neonatal parameters and the variable severity of above mentioned sequelae. Methods We have recruited 32 subjects, whose history and neuroimages suggested a perinatal H.I.E and we have retrospectively analysed clinical-instrumental parameters at birth and at one year of age. Results At one year cut-off, 9 patients developed both secondary epilepsy and CP (28%), whereas the other subjects showed only motor delay (31%), only secondary epilepsy (3%) or only CP (38%). Patients with both the severest sequelae were essentially term infants (only 2/9 were pre-term infants), with normal weight (only 3 LBW) and 7 of them with early pathologic EEG and neuroimages pointing out cortex injuries (typical of term infants). A statistic analysis showed the following correlations: birth weight and global prognosis (χ2 = 14,03; p = 0,04); neonatal clinical pattern and CP's severity (χ2 = 14,03; p = 0,0009); early EEG and CP's severity (χ2 = 4,32; p = 0,04); epileptic onset age and CP and Epilepsy's severity (F = 16,01; p = 0,005). Birth weight represented a predictive factor of early neurological outcome (<1,5 kg birth weight neonates are not at risk of both epilepsy and CP); neonatal clinical pattern and early EEG were correlated with variable severity of CP; an epileptic exordium in the first 6 months led up to a more severe epileptic and paretic outcome. Conclusion From a clinical point of view it is of crucial importance to have some parameters which enable to discriminate patients at risk of more severe sequelae from those at risk of moderate severity outcome.